Assessment of Heavy Metal on Nasipit Port - Tamayo, Frank Kinneth; Bahian, Arnel; Agsoy, Dexter; Amparo, Dexter; Felias , Angelo; Rele, Daniel Louis; Tima, Genesis (JPAIR Multidisciplinary Research, 2024)
This study aimed to assess the presence of heavy metals, specifically Cadmium (Cd), Copper (Cu), Lead (Pb), Magnesium (Mg), Nickel (Ni), and Silver (Ag), in Nasipit Port, Nasipit, Agusan Del Norte, Philippines. The study measured and quantified the concentrations of these heavy metals in various environmental compartments within and around the port area, including water and sediment samples. This study employed an experimental research design to investigate the presence of heavy metals in Nasipit Port. The research utilized DOST’s laboratory equipment and did not involve human respondents. The sampling method involved measuring the distance from the ship to collect water and sediment samples. The study ensured informed consent, voluntary participation, and privacy protection for the participants. The results showed that Cadmium, Copper, Lead, and Nickel were not detected, while Magnesium and Silver exceeded the standard limits set by the DENR. The study found no significant difference in heavy metal contamination between areas with and without ships, indicating that the port is still classified as safe for ecological risk assessment. The recommendations emphasize the importance of community engagement, continuous monitoring, and public awareness to protect the marine ecosystem and public health. Finally, future researchers are encouraged to expand the study to include other heavy metals and investigate their bioaccumulation in fish and other marine organisms.